2016
DOI: 10.5267/j.msl.2016.5.001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quality of electronic banking services on agility of a bank

Abstract: Studies have shown that in service organizations, quality can have a growth in customer satisfaction as its consequence, and when it regards the banking services, factors are brought up with regard to the quality of banking services, which include the speed in responding, providing products proportionate to the customer needs, and gaining competence. These concepts are shared by the issue of organizational agility; hence, the qualities as well as the bank's agility of the banking system embrace these concepts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Most recent works on service quality (Pizam et al, 2016;Pourmohammad et al, 2016;Baumann et al, 2017;Lan et al, 2016) are variants of different modifications by many researchers in an attempt to solve one of the criticisms that the five-dimension constructs in Parasuraman et al (1988) are not a standard measure for customers' satisfaction. The works of Mohammad andAlhamadani (2011), Oh et al (2017), Wan et al (2016) and Murali et al (2016) are an example of such modification on SERVQUAL investigating the level and effect of service quality on customer satisfaction using multiple regression analysis to test the impact of service quality on customer satisfaction based on nine items adapted from Lassar et al (2000) and the outcome of the distribution of 260 questionnaires among customers of commercial bank in Jordan showed that service quality is a function of customer satisfaction.…”
Section: Related Workmentioning
confidence: 99%
“…Most recent works on service quality (Pizam et al, 2016;Pourmohammad et al, 2016;Baumann et al, 2017;Lan et al, 2016) are variants of different modifications by many researchers in an attempt to solve one of the criticisms that the five-dimension constructs in Parasuraman et al (1988) are not a standard measure for customers' satisfaction. The works of Mohammad andAlhamadani (2011), Oh et al (2017), Wan et al (2016) and Murali et al (2016) are an example of such modification on SERVQUAL investigating the level and effect of service quality on customer satisfaction using multiple regression analysis to test the impact of service quality on customer satisfaction based on nine items adapted from Lassar et al (2000) and the outcome of the distribution of 260 questionnaires among customers of commercial bank in Jordan showed that service quality is a function of customer satisfaction.…”
Section: Related Workmentioning
confidence: 99%